2019
DOI: 10.3389/fendo.2019.00696
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Estradiol Rise After Dual Trigger in Progestin-Primed Ovarian Stimulation Is Associated With a Lower Oocyte and Mature Oocyte Yield in Normal Responders

Abstract: Background: Prior studies have shown that patients with a >10% estradiol (E2) rise after trigger had more oocytes retrieved than plateauing or decreasing E2 responders. However, multiple follicles develop at different stages of maturation during controlled ovarian stimulation (COS) and may exhibit different responses to trigger. The association between the magnitude of E2 increase and oocyte retrieval outcomes is still unclear.Methods: This was a retrospective cohort study of 2,898 women undergoing their first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…The majority of study participants in all groups were between the ages of 25 and 34 years, were overweight, and had been experiencing infertility for less than five years at the time of enrollment. These findings were close to that reported by Decleer, et al, 7 in a study done earlier showed that, covariates, age, body mass index (BMI), basal hormonal level, the number of days of stimulation as well as the cycle ranking did not demonstrate any differences between the groups compared. In another study, Lamb et al 3 discovered that the mean age of women undergoing ART therapy was 30.36 years, and that the mean BMI was 25.9 kilograms per square meter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of study participants in all groups were between the ages of 25 and 34 years, were overweight, and had been experiencing infertility for less than five years at the time of enrollment. These findings were close to that reported by Decleer, et al, 7 in a study done earlier showed that, covariates, age, body mass index (BMI), basal hormonal level, the number of days of stimulation as well as the cycle ranking did not demonstrate any differences between the groups compared. In another study, Lamb et al 3 discovered that the mean age of women undergoing ART therapy was 30.36 years, and that the mean BMI was 25.9 kilograms per square meter.…”
Section: Discussionsupporting
confidence: 92%
“…When properly indicated, intrauterine insemination (IUI) is a less invasive and more affordable alternative to other methods of conception. [5][6][7] The aim of the study was to determine whether dual trigger (FSH and hCG) can improve the ovulation and pregnancy rate (Figure 1).…”
Section: Research Articlementioning
confidence: 99%
“…The results of early studies of IVF cycles showed that E2 values measured 24 h after hCG administration are not predictive of reproductive outcome ( 15 , 16 ) . Ozdegirmenci et al ( 15 ) reported a 38% CPR in women with a 30% E2 decline, but in Huang’s study ( 16 ) , the number of women with a 30% decrease was too small to allow a statistical comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it significantly reduces the occurrence of ovarian hyperstimulation syndrome (OHSS), a severe complication associated with other COH protocols. Due to these benefits, the PPOS protocol is considered suitable for women with various ovarian responses, including those with poor ovarian response (3)(4)(5)(6), normal responders (7,8), and even high responders (7,9) in IVF/ICSI cycles.…”
Section: Introductionmentioning
confidence: 99%